Recent development of hypertension and acute renal failure in a 59-year-old woman - Uebner, M.; Jacobi, Johannes; Schmidt, D.; Büttner-Herold, M.; Mackensen, Andreas; Spriewald, B. M. (Internist, 2017)
We report on a 59-year-old woman who presented with nausea, fatigue, arterial hypertension, and acute renal failure. Clinical examination, laboratory findings of blood and urine and abdominal sonography were inconclusive. Renal biopsy revealed infiltration by a diffuse large B-cell lymphoma. In fluorodeoxyglucose positron emission tomography/computed tomography tracer enrichment was demonstrated in both kidneys, skeletal system and retroperitoneal lymph nodes. Renal function improved already after the first cycle of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone). After chemotherapy, a complete remission, normalization of blood pressure and renal function were achieved.
EVALuna2:25508